2018
DOI: 10.1002/adma.201801612
|View full text |Cite
|
Sign up to set email alerts
|

Spinel Structural Disorder Influences Solar‐Water‐Splitting Performance of ZnFe2O4 Nanorod Photoanodes

Abstract: Zinc spinel ferrite, ZnFe O (ZFO), is an emerging photoanode material for photoelectrochemical (PEC) solar fuel production. However, a lack of fundamental insight into the factors limiting the photocurrent has prevented substantial advance in its performance. Herein, it is found that ZFO nanorod array photoelectrodes with varying crystallinity exhibit vastly different PEC properties. Using a sacrificial hole scavenger (H O ), spatially defined carrier generation, and electrochemical impedance spectroscopy, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 42 publications
(54 reference statements)
3
120
0
Order By: Relevance
“…Other configurations between normal and inverse are commonly observed and the degree of inversion, x, is the parameter employed to describe them according to T [M 1– x Fe x ] O [M x Fe 2– x ]O 4 , where 0 ≤ x ≤ 1. Among spinel ferrites, zinc ferrite (ZnFe 2 O 4 , ZFO) is widely studied due to its promising application in photoelectrochemistry as a photoanode material for solar‐light‐driven water oxidation ,. The thermodynamically most stable configuration of ZFO at 273.15 K and 100 kPa is the normal spinel structure ( x =0) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other configurations between normal and inverse are commonly observed and the degree of inversion, x, is the parameter employed to describe them according to T [M 1– x Fe x ] O [M x Fe 2– x ]O 4 , where 0 ≤ x ≤ 1. Among spinel ferrites, zinc ferrite (ZnFe 2 O 4 , ZFO) is widely studied due to its promising application in photoelectrochemistry as a photoanode material for solar‐light‐driven water oxidation ,. The thermodynamically most stable configuration of ZFO at 273.15 K and 100 kPa is the normal spinel structure ( x =0) .…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al. have recently reported that ZFO samples with poor crystallinity and a high degree of inversion exhibit a higher efficiency for the photoelectrochemical water oxidation than samples with higher crystallinity and low degree of inversion . Other authors have investigated the influence of the grain size and the synthetic conditions on the electrical properties of ZFO .…”
Section: Introductionmentioning
confidence: 99%
“…[147] )c )Currentdensityv ersus PE potential curves of the nanocore Mo:BiVO 4 film measured in ap hosphateb uffer solutionc ontaining0 .5 m Na 2 SO 3 (with SO 3 2À as as acrificial oxidant) and the nanocone Mo:BiVO 4 /Fe(Ni)OOH film measured in phosphate buffer solution.R eproduced with permission. [149] ) ChemSusChem 2019, 12,4337 -4352 www.chemsuschem.org [148] )d )Linear scanning photocurrentdensityv ersus electrode potential curveso fZnFe 2 O 4 (zinc spinel ferrite, ZFO)n-PE in 1 m NaOHu nder intermittent simulatedi llumination of one sun (100 mW cm À2 ).…”
Section: Wide Band Gap Metal Oxidesmentioning
confidence: 99%
“…Lee et al found that thermalt reatment under hydrogen or vacuum couldb oost the photoactivity by up to 20 times. [149] By adjusting the formation temperature, which has as ignificant impact on crystal structure, they obtained a benchmark j ph of 1.0 mA cm À2 at 1.23 Vv ersusR HE with a nickel-iron oxide as an additional catalystt of acilitate the oxygen evolution reaction (Figure 6d). [113] Doping was also achieved by the group of Zou through spray pyrolysis.…”
Section: Spinel Ferritesmentioning
confidence: 99%
See 1 more Smart Citation